Notes on Calculus and Optimization

Notes on Calculus and Optimization

Economics 101A Section Notes GSI: David Albouy Notes on Calculus and Optimization 1 Basic Calculus 1.1 Definition of a Derivative Let f (x) be some function of x, then the derivative of f, if it exists, is given by the following limit df (x) f (x + h) f (x) = lim − (Definition of Derivative) dx h 0 h → df although often this definition is hard to apply directly. It is common to write f 0 (x),or dx to be shorter, or dy if y = f (x) then dx for the derivative of y with respect to x. 1.2 Calculus Rules Here are some handy formulas which can be derived using the definitions, where f (x) and g (x) are functions of x and k is a constant which does not depend on x. d df (x) [kf (x)] = k (Constant Rule) dx dx d df (x) df (x) [f (x)+g (x)] = + (Sum Rule) dx dx dy d df (x) dg (x) [f (x) g (x)] = g (x)+f (x) (Product Rule) dx dx dx d f (x) df (x) g (x) dg(x) f (x) = dx − dx (Quotient Rule) dx g (x) [g (x)]2 · ¸ d f [g (x)] dg (x) f [g (x)] = (Chain Rule) dx dg dx For specific forms of f the following rules are useful in economics d xk = kxk 1 (Power Rule) dx − d ex = ex (Exponent Rule) dx d 1 ln x = (Logarithm Rule) dx x 1 Finally assuming that we can invert y = f (x) by solving for x in terms of y so that x = f − (y) then the following rule applies 1 df − (y) 1 = 1 (Inverse Rule) dy df (f − (y)) dx Example 1 Let y = f (x)=ex/2, then using the exponent rule and the chain rule, where g (x)=x/2,we df (x) d x/2 d x/2 d x x/2 1 1 x/2 get dx = dx e = d(x/2) e dx 2 = e 2 = 2 e . The inverse function of f can be gotten · x/2 x/2 x x by solving for x in terms of y. y = e ln y =ln e = 2 ln (e)= 2 x =2lny using the facts ¡ ¢ u ¡ ¢ ¡ ⇒¢ ¡ ¢ 1⇒ from precalculus that ln e = u ln e and that ln e =1. The derivative of f − (y) can be solved directly as 1 d d 1 2 ¡ ¢ df − (y) 1 1 dy (2 ln y)=2dy (ln y)=2 y = y or indirectly through the Inverse Rule as dy = 1 x/2 = 1 2lny/2 = 2 e 2 e 2 2 ln y ln y = using the fact that³e ´ = y. e y 1 y x 5 10 2.5 7.5 0 0 2.5 5 7.5 10 5 y -2.5 2.5 0 -5 -5 -2.5 0 2.5 5 x dy 1 x =2lny dx = 2 y =exp(x/2) dx = 2 exp (x/2) dy y 1.3 Partial Differentiation Taking derivatives of functions in several variables is very straightforward (at least with the functions used in economics). Say we have a function in two variables, x and y,whichwecanwriteash (x, y). Partial differentiation, which uses a "∂" ("del") instead of a "d", can be done in either in x or in y,bywritingeither ∂ ∂ " ∂x"or"∂y "infrontofh (x, y), respectively, and then taking the derivative with respect to the variable chosen as we would in the single variable case, treating the other variable as a constant. Example 2 Let h (x, y)=3x2 ln y, shown below in the graphs for ranges 0 x 2 and 0 y 10 ≤ ≤ ≤ ≤ y 10 h(x,y) 20 7.5 10 57.5 y 02.50.25 0.5 0.75 1 1.25 1.5 1.75 2 x 5 -20 2.5 -40 0.5 1 1.5 2 x 3-D representation of 3x2 ln y Level curves 3x2 ln y = k for k =1, 2,...,27 Note the second plot of the level curves are like what you would find in a topographic contour map. Applying the partial differentiation rules we get the partial derivatives ∂ ∂ 3x2 ln y =3lny x2 =3lny (2x)=6x ln y ∂x ∂x µ ¶ ∂ ¡ ¢ ∂ 1 3x2 3x2 ln y =3x2 ln y =3x2 = ∂y ∂y y y µ ¶ µ ¶ ¡ ¢ 2 1.4 Total Differentiation Say that we know already that y is a function of x,sayy = f (x) and we want to see how a function in both variables, say h (x, y) responds when we let both x change and y change according to how it should according to f. The we could rewrite our expression as a function in a single variable H (x)=h (x, f (x)) and take the total derivative with respect to x to get dH (x) ∂h(x, f (x)) ∂h(x, f (x)) df (x) = + (Total Derivative) dx ∂x ∂y dx where the second term makes use of the chain rule. x/2 2 df (x) 1 x/2 Example 3 Let y = f (x)=e and again h (x, y)=3x ln y.Thendx = 2 e .Andsobythe dH(x) 3x2 1 x/2 above formulas we have dx =6x ln y + y 2 e . Notice that this expression is in both x and y.It x/2 dH(x) x/2 3x2 1 x/2 can be simplified to be just a function of x by substituting in y = e so dx =6x ln e + ex/2 2 e = 2 3x2 9 2 3x + 2 = 2 x . Of course had we substituted in directly for y from the beginning we would have gotten 2 x/2 3 3 dH(x) 9 2 H (x)=3x ln e = 2 x and differentiating directly dx = 2 x , but this is not as general a treatment. y 10 h(x,y) 20 7.5 10 57.5 y 02.50.25 0.5 0.75 1 1.25 1.5 1.75 2 x 5 -20 2.5 -40 0.5 1 1.5 2 x exp (x/2) crossing level curves h (x, f (x)) is given by curve on the surface 1.5 Implicit Differentiation Imagine that it is known that y depends on x, but that we do not have an "explicit" formula for y in terms of x, but that we do know that together x and y must satisfy some equation h (x, y)=k (Equation in 2 variables) where h (x, y) is a function and k is just a constant (any equation in x and y can be written like this). Sometimesitisdifficult to solve "explicitly" for y in terms of x, i.e. to find the function f such that y = f (x). Nevertheless by the implicit function theorem we can still findthederivativeoff by differentiating "implicitly" with respect to x,treatingy as a function of x,sowecanwrite H (x)=h (x, f (x)) = k Using what we learned about total differentiation we can differentiate totally with respect to x to get dH (x) ∂h(x, f (x)) ∂h(x, f (x)) df (x) = + =0 dx ∂x ∂y dx df (x) andthensolvingfor dx we get df (x) ∂h(x,f(x)) = ∂x (Implicit Derivative) dx − ∂h(x,f(x)) ∂y Note that this trick does not work if ∂h(x,f(x)) =0since the derivative is undefined. ∂y 3 Example 4 Assume that our equation is h (x, y)=3x2 ln y =3. Thenusingthederivativewetookabove 2 2 we have dH(x) =6x ln y+ 3x df (x) =0.Solvingfordf (x) we get df (x) = (6x ln y) / 3x . This expression dx y dx dx dx − y is in both x and y, but we could evaluate it meaningfully for any value of x and y satisfying³ ´ 3x2 ln y =3for df (1) 3 instance x =1and y = e which means that dx = (6 1) / e = 2e. Of course this derivative may be different for different values of x. − · − ¡ ¢ y 10 7.5 5 2.5 0.5 1 1.5 2 x Implicit derivative at x =1,y = e is 2e − 2 Optimization 2.1 Increasing and Decreasing Functions By looking at the definition of a derivative we can say "loosely speaking" that for h small h 0 and positive h>0 that ≈ df (x) f (x + h) f (x) − dx ≈ h or that df (x) h = f (x + h) f (x) dx − Now we say that a function f is increasing at x if we have f (x + h) >f(x) or f (x + h) f (x) > 0. df (x) − However since h>0 this implies that dx > 0. Equivalently a function f is decreasing at x if we have df (x) f (x + h) <f(x) which then implies that dx < 0. Therefore the sign of the derivative tells us whether or not a function is increasing (the derivative is positive) or decreasing (the derivative is negative). 2.2 Unconstrained Optimization 2.2.1 One Variable Consider first the case with one variables x where x R,i.e. x cantakeonanyrealvalue. Wewishto maximize the objective function f (x) and there are∈ no constraints. Thus we solve max f (x) x Assuming f (x) has a maximum (for example f does not go to )1 andthatitisdifferentiable everywhere, ∞ then any maximum (x∗) must solve the following first order necessary conditions (FOC) df (x ) ∗ =0 (FOC) dx 1 Weierstrauss’s Theorem say shat f (x, y) will be guaranteed to have a maximum if f is continuous and x and y are defined over a closed and bounded domain.

View Full Text

Details

  • File Type
    pdf
  • Upload Time
    -
  • Content Languages
    English
  • Upload User
    Anonymous/Not logged-in
  • File Pages
    10 Page
  • File Size
    -

Download

Channel Download Status
Express Download Enable

Copyright

We respect the copyrights and intellectual property rights of all users. All uploaded documents are either original works of the uploader or authorized works of the rightful owners.

  • Not to be reproduced or distributed without explicit permission.
  • Not used for commercial purposes outside of approved use cases.
  • Not used to infringe on the rights of the original creators.
  • If you believe any content infringes your copyright, please contact us immediately.

Support

For help with questions, suggestions, or problems, please contact us